Social value: Quantitatively measurable - Torres, Paula; Ferrer, Rosa (Omnia, 2025)
The objective of this research was to determine to what extent social value is promoted with the application of Problem-Based Learning as a teaching strategy, from the teaching of chemistry. The research methodology was based on a descriptive positivist approach, using the survey and questionnaires with a Likert scale as data collection techniques and instruments, managing to apply Student’s T for two samples assuming unequal variances, with a significance level of 5%, according to the level established in the social sciences. The non-probabilistic and intentional sample was made up of 20 students from the 3rd year of secondary education at Nuestra Señora de Guadalupe School. The information collected allowed us to conclude that the application of Problem-Based Learning significantly promotes the skill of Social Value.